The effect of hepatitis C virus treatment on ovarian reserve - Midan, Mahmoud F.; Eid, Samia M.; El-Latif, Mahmoud A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The hepatitis C treatment effect on ovarian reserve of the treated women and so on their reproductive potential attracting the attention and becoming an issue of concern. In this study, we examine the possible action of interferon and ribavirin regimen on the ovarian reserve through assessing the change of AMH level pre-and post-treatment. Methods: This study is a prospective longitudinal one, includes fifty women in childbearing period with chronic HCV infection fulfilling the criteria of attending the Egyptian national program for HCV treatment and has been referred for antiviral therapy with PEG IFN-α2a or PEG IFN-α2b, plus oral ribavirin for a total of 48 weeks. All patients were tested to AMH level at the beginning of the treatment program (the mean AMH level was 1ngml-3ngml) and retested at the end of treatment program. In addition, they examined by vaginal ultrasound to measure ovarian volume. Results: At the end of the treatment program 28% of the studied cases remain within pre treatment level of AMH & in 32% of the studied cases the level of AMH decreased where’s in 40% of the studied cases the level of AMH increased. Conclusions: It is likely that interferon and ribavirin affect ovarian reserve of treated patients as a change occurs in the level of AMH in 72% of them.